2018
DOI: 10.1080/15440478.2018.1477084
|View full text |Cite
|
Sign up to set email alerts
|

Impact behavior of sandwich structures made of flax/epoxy face sheets and agglomerated cork

Abstract: The unremitting quest of natural and renewable materials able to replace their synthetic counterparts in high-performance applications has involved also sandwich structures. In this regard, the aim of this work is to characterize the impact response, in both high-and low-velocity conditions, of green sandwich structures made of agglomerated cork as core and flax/epoxy laminates as face sheets. Both bare cork, flax skins, and complete sandwich structures were subjected to impacts at three different energy level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…To obtain this velocity, a least-squares method was used, by fitting Equation (1) which is similar to that proposed in the model of Recht and Ipson [39]. This method has been used successfully to predict the minimum perforation velocity in laminate and sandwich structures subjected to high velocity impacts [30,[40][41][42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain this velocity, a least-squares method was used, by fitting Equation (1) which is similar to that proposed in the model of Recht and Ipson [39]. This method has been used successfully to predict the minimum perforation velocity in laminate and sandwich structures subjected to high velocity impacts [30,[40][41][42].…”
Section: Resultsmentioning
confidence: 99%
“…Sanchez-Saez et al [29] observed a great capacity to absorb energy even after several consecutive impacts. In addition, Sarasini et al [30] observed in their studies that the absorption of energy in high deformations can be quite considerable without signs of breaking of the cell walls, because an almost complete recovery of their original shape and size occurs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the employment of two different specimen supports allowed to disclose the effect of boundary conditions highlighting a different impact susceptibility not only of the complete sandwich structures, but also of the sole cores and skins as a function of sample constraints. Concerning the ballistic behavior, Sarasini et al [146] and Sanchez-Saez et al [147] already addressed the topic investigating flax/epoxy and aluminum face sheets sandwich panels response, respectively. To further increase the data base in this field, some parameters neglected in the previous works were evaluated, i.e.…”
Section: Novelty and Implicationsmentioning
confidence: 99%
“…Among these green composites, the flax-reinforced biobased composites have been widely studied in recent years [ 18 , 19 , 20 , 21 ] due to the fact that flax fibre possesses high strength and stiffness in comparison to other natural plant fibres. For the “skin” material of the sandwich structure, flax fibres can be attractive alternatives due to the excellent properties of flax fibres [ 22 ]. For the “core” material, cork, a cellular material obtained from the bark of Cork Oak trees, can serve as an ideal material because it is 100% biodegradable and renewable with advantages, including low density, high shear modulus, damping ratio and impact resistance.…”
Section: Introductionmentioning
confidence: 99%